An Investigation of Episodic Memory for Item and Associative Information in Aging - Thiede, Emily (The University of Edinburgh, 2013)
This study aimed to explore to what extent the memory difficulties in older adults are a result of problems with memory control and the role played by associative memory in age-related changes. This project explored participants’ ability to encode and retrieve sets of word pairs, and the effect of word relatedness on their performance. This was in order to understand better how the automatic and controlled influences on associative memory change in aging. In order to answer these questions, younger and older adults were compared, focusing particularly on associative memory tasks. Comparisons were drawn between older and younger adults’ item and associative memory using word pair recognition tasks and the additional variable of word pair relatedness. Participants were drawn from two age groups with younger adults’ ages ranging from 18 to 33 and older adults’ from 60 to 75. There were two phases, an encoding phase followed by a retrieval phase, to each test. Participants were presented with word pairs in the encoding phase and given an opportunity to encode the information by rating the perceived association between the two words. The retrieval phase either involved pair recognition (determining whether the whole word pair was presented in the same combination as at encoding) or item recognition (determining whether the second word in the pair appeared in the encoding phase). The main results of this study show an overall memory deficit and decrement in performance with age with an improvement with relatedness in both age groups. There was a higher number of false alarms for the rearranged condition in older adults in the pair task, along with a lower number of hits for old word pairs, suggesting diminished ability to distinguish between old and recombined pairs, demonstrating an associative deficit in the pair task. These findings suggest further evidence for the importance of support (relatedness) in age-related memory decline.
Keywords: Memory; Aging